ANALYSIS OF INFORMATION TECHNOLOGY CRIME AND CRIMINAL LAW ENFORCEMENT POLICY EFFORTS IN THE ERA OF GLOBALIZATION - Devinda S; Rizqyta P. K; Cindy Firdiani; Tomasia Da Costa; Shifa S. S; Chelsea Z.P. G (Problematika Hukum, 2023)
The era of globalization influences the development of technologyand the internet for human life. Cybercrime can be carried out as a form of crime by involving several perpetrators in several jurisdictions of different countries, with target victims in other countries as well. This study analyzes the laws and regulations related to cybercrime in Indonesia, namely, the Criminal Code, the Telecommunications Law, the ITE Law, and the Draft Criminal Code which will become legislation in Indonesia and is based on comparative law and descriptive analysis. The research methodology uses qualitative normative legal methods with a literature study. This research also uses descriptive specifications to describe criminal law enforcement policies in eradicating information technology crimeKeywords:Globalization, Information Technology, Cyber Crime, Criminal Law Enforcement Policy